Bioactive compounds from the Pantanal biome: a review (Research, Society and Development, 2022)
The Pantanal is the largest floodplain in the world, occupying the territory of four western countries, rich in biodiversity and has a vast flora that presents natural compounds with functional properties that go beyond their intrinsic properties. The aim of this study was to investigate in the literature the existence of bioactive compounds in the Brazilian wetland biome. Scientific articles published between 2018 and 2022 were collected in the electronic databases Science Direct, Scientific Electronic Library Online and National Library of Medicine. Nineteen plants were found where the main bioactive compounds were phenolics, flavonoids, polyphenols and terpenes. The plants showed several beneficial activities for human use as antioxidant, antimicrobial and anti-inflammatory, and can be considered for use in the food, cosmetic and pharmaceutical industries.